Training and Assessing Critical Airway, Breathing, and Hemorrhage Control Procedures for Trauma Care: Live Tissue Versus Synthetic Models. (14th December 2017) - Hart, Danielle; Rush, Robert; Rule, Gregory; Clinton, Joseph; Beilman, Gregory; Anders, Shilo; Brown, Rachel; McNeil, Mary Ann; Reihsen, Troy; Chipman, Jeffrey; Sweet, Robert
Abstract: Introduction: Optimal teaching and assessment methods and models for emergency airway, breathing, and hemorrhage interventions are not currently known. The University of Minnesota Combat Casualty Training consortium (UMN CCTC) was formed to explore the strengths and weaknesses of synthetic training models (STMs) versus live tissue (LT) models. In this study, we compare the effectiveness of best in class STMs versus an anesthetized caprine (goat) model for training and assessing seven procedures: junctional hemorrhage control, tourniquet (TQ) placement, chest seal, needle thoracostomy (NCD), nasopharyngeal airway (NPA), tube thoracostomy, and cricothyrotomy (Cric). Methods: Army combat medics were randomized to one of four groups: 1) LT trained–LT tested (LT‐LT), 2) LT trained–STM tested (LT‐STM), 3) STM trained–LT tested (STM‐LT), and 4) STM trained–STM tested (STM‐STM). Participants trained in small groups for 3 to 4 hours and were evaluated individually. LT‐LT was the "control" to which other groups were compared, as this is the current military predeployment standard. The mean procedural scores (PSs) were compared using a pairwise t‐test with a Dunnett's correction. Logistic regression was used to compare critical fails (CFs) and skipped tasks. Results: There were 559 subjects included. Junctional hemorrhage control revealed no difference in CFs, but LT‐tested subjects (LT‐LT and STM‐LT) skipped this task more than STM‐tested subjects (LT‐STM and STM‐STM; p < 0.05), and STM‐STM had higher PSs than LT‐LT (p < 0.001). For TQ, both STM‐tested groups (LT‐STM and STM‐STM) had more CFs than LT‐LT (p < 0.001) and LT‐STM had lower PSs than LT‐LT (p < 0.05). No differences were seen for chest seal. For NCD, LT‐STM had more CFs than LT‐LT (p = 0.001) and lower PSs (p = 0.001). There was no difference in CFs for NPA, but all groups had worse PSs versus LT‐LT (p < 0.05). For Cric, we were underpowered; STM‐LT trended toward more CFs (p = 0.08), and STM‐STM had higher PSs than LT‐LT (p < 0.01). Tube thoracostomy revealed that STM‐LT had higher CFs than LT‐LT (p < 0.05), but LT‐STM had lower PSs (p < 0.05). An interaction effect (making the subjects who trained and tested on different models more likely to CF) was only found for TQ, chest seal, and Cric; however, of these three procedures, only TQ demonstrated any significant difference in CF rates. Conclusion: Training on STM or LT did not demonstrate a difference in subsequent performance for five of seven procedures (junctional hemorrhage, TQ, chest seal, NPA, and NCD). Until STMs are developed with improved anthropomorphic and tissue fidelity, there may still be a role for LT for training tube thoracostomy and potentially Cric. For assessment, our STM appears more challenging for TQ and potentially for NCD than LT. For junctional hemorrhage, the increased "skips" with LT may be explained by the differences in anatomic fidelity. While these results begin to uncover the effects of training and assessing these procedures on various models, further study is needed to ascertain how well performance on an STM or LT model translates to the human model.